Strategic Leadership Management Analysis for Sustainable Corporate Development: Analisis Manajemen Kepemimpinan Strategik untuk Perkembangan Perusahaan yang Berkelanjutan - Naba Fahlan Yakub (PT Syamilah Literasi Islami, 2024)
In every organization, whether an institution or a company, there must be at least someone who is a leader in the organization's activities. In leadership, he has the task of determining a strategic policy taken that can affect the sustainability of an organization. In leadership, he has the task of determining a strategic policy taken that can affect the sustainability of an organization. A company can move forward or vice versa depending on how a policy from the leader can impact the company. The right strategic leadership will be indispensable to sustainably develop a company. This strategic policy is related to various things that are further expected to make the company develop more sustainably. This study will discuss how a strategic leadership can develop a company sustainably by paying attention to three factors: human resource management, company management, and leadership itself. Human resources are people in an organization or company starting with all levels in it, then company management which means all forms of management and standardization of work in a company, and in leadership blessed with a leadership style and the application of a clear structure in a company.